Real-life use of delamanid: results from the European post-authorisation safety study - N. Schönfeld; L. Barkane; I. Davoliene; M. Danilovits; S. Miliauskas; F. Ader; O.M. Kon; C. Lange; A. Duvignaud; M. Heiss-Neumann; N. Hittel; N. Lazarević; et al. (IJTLD Open)
BACKGROUND: A post-authorisation safety study (PASS) on delamanid (DLM) was conducted as part of a post-approval commitment to the European Medicines Agency. The aim of this study was to evaluate the use of DLM in a real-life setting, its safety, and treatment outcomes in patients with multidrug-resistant TB (MDR-TB).METHODS: This was a prospective, multicentric, non-interventional study conducted in the European Union. MDR-TB Regimen selection and patient monitoring were conducted in accordance with existing medical practices. Data on the use of DLM, related adverse events, and treatment outcomes were collected for up to 30 months after the first DLM dose. Descriptive summary statistics were used for continuous and categorical variables.RESULTS: Out of 86 patients, one had extrapulmonary TB. Two-thirds of the patients were treated with DLM for more than 24 weeks. The most frequent adverse drug reaction to DLM was QT interval prolongation. Resistance to DLM was detected in one patient during treatment. The treatment success rate was 77%.CONCLUSION: No new safety concerns were revealed, including in patients treated with DLM for more than 24 weeks. QT interval prolongations were well managed and did not lead to any clinically significant cardiac effects. The treatment outcomes were in line with the WHO target for Europe.